Middle latency auditory evoked potential in child population - de Oliveira, Anna Caroline Silva [UNESP]; Regaçone, Simone Fiuza [UNESP]; Frizzo, Ana Claudia Figueiredo [UNESP] (Faculdade de Filosofia e Ciências, 2016)
Introduction: The middle-latency auditory evoked potential is used to evaluate any abnormality that might impair the central auditory pathways, which are situated between the brain stem and the primary auditory cortex. Objective: To analyse the middle-latency auditory evoked potentials in children. Methods: This is a descriptive and cross-sectional study. Pure-tone audiometry was performed, and if no change was detected, Biologic's portable Evoked Potential System (EP) was used to measure auditory evoked potentials. The identification of the responses was performed using electrodes positioned at C3 and C4 (left and right hemispheres) in reference to ears A1 and A2 (left and right earlobe). These were ipsilaterally and contralaterally paired and landed at Fpz (forehead), in two steps, with alternating stimulation of the right and left ears. Results: In this study, there was 100% detectability of the Na, Pa, and Nb components and interamplitude Na-Pa. This study compared different electrode leads, and there was no significant difference between the different electrode positions studied for the right and left ears in the studied population. Conclusion: It was concluded that the examination of middle-latency evoked potential is steady and feasible for the studied age group regardless of electrode position.
Keywords: Auditory evoked potential; Auditory evoked responses; Children